The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1007/s11325-015-1223-x
|View full text |Cite
|
Sign up to set email alerts
|

Comorbid depression in obstructive sleep apnea: an under-recognized association

Abstract: Depression is prevalent among patients with OSA both in the community and in sleep disorder clinics. Clinicians in general should be aware of this significant association and should aim to treat both disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
65
3
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(79 citation statements)
references
References 68 publications
6
65
3
5
Order By: Relevance
“…Unlike other studies using the SCL-90-R, we found that patients with great daytime sleepiness and cognitive complaints have increased values of anxiety, depression, obsession and interpersonal sensitivity symptoms (BaHammam et al, 2015). Actually, recent research refers that the OSAS can be associated with less vigour, diminished interest or pleasure, decreases in social contacts, poor compliance with treatments and less ability to perform cognitive tasks requiring alternative options, for instance, eating behaviour (Sforza, de Saint Hilaire, Pelissolo, Rochat, & Ibanez, 2002).…”
Section: Discussioncontrasting
confidence: 75%
See 1 more Smart Citation
“…Unlike other studies using the SCL-90-R, we found that patients with great daytime sleepiness and cognitive complaints have increased values of anxiety, depression, obsession and interpersonal sensitivity symptoms (BaHammam et al, 2015). Actually, recent research refers that the OSAS can be associated with less vigour, diminished interest or pleasure, decreases in social contacts, poor compliance with treatments and less ability to perform cognitive tasks requiring alternative options, for instance, eating behaviour (Sforza, de Saint Hilaire, Pelissolo, Rochat, & Ibanez, 2002).…”
Section: Discussioncontrasting
confidence: 75%
“…The overlap of the OSAS and depression may also worsen the severity of the disease; the prevalence of depression in the OSAS's clinical populations varies widely from 7% to 63% (BaHammam et al, 2015;Douglas et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Obstructive sleep apnea (OSA) is more common in pregnancy,73 and OSA is associated with an increased risk of gestational hypertension, intrauterine growth retardation, and gestational diabetes mellitus 73. OSA is associated with major depression in the general population; longitudinal studies show an increased risk of developing major depression in patients with OSA, and severity of OSA is related to the risk of developing major depression 74. Continuous positive airway pressure (CPAP) has been found to improve symptoms of depression in OSA patients with comorbid depression in some but not all studies of major depression in non-pregnant patients 7576…”
Section: Personalized Treatment For Specific Clinical Characteristicsmentioning
confidence: 99%
“…(4) tarafından bildirilmiş olup takip eden yıllar boyunca pek çok çalışmada OUAS ile yaşam kalitesinde bozulma, depresyon ve mod değişiklikleri arasında pozitif bir ilişki olduğu gösterilmiştir (5)(6)(7)(8)(9)(10)(11)(12)(13)(14). Yapılan çalışmalarda OUAS'li hastalarda depresyon sıklığı %5-63 gibi değişen oranlarda bulunmuştur (11). Bu çalışmalar arasında depresyonun OUAS şiddeti ile ilişkili olduğunu tespit edenlerin yanı sıra hastalığın şiddetinden bağımsız olarak GAU gibi semptomlar ile ilişkili olduğunu gösterenler de mevcuttur.…”
Section: Introductionunclassified
“…Bu çalışmalar arasında depresyonun OUAS şiddeti ile ilişkili olduğunu tespit edenlerin yanı sıra hastalığın şiddetinden bağımsız olarak GAU gibi semptomlar ile ilişkili olduğunu gösterenler de mevcuttur. Bu tartışmalar bu konuda yapılmış ilk çalışmalardan günümüze kadar halen devam etmektedir (5,9,11,13). Çalışmalarda hastalardaki mod değişikliklerini tespit etmek için yaşam kalitesi ve depresyonu ölçen çeşitli skalalar kullanılmıştır.…”
Section: Introductionunclassified